GAMBARAN KUALITAS VISUM ET REPERTUM PERLUKAAN DI RUMAH SAKIT BHAYANGKARA MEDAN - ZUHRA AQILA RANGKUTI; ABDUL GAFAR PARINDURI (JURNAL ILMIAH MAKSITEK, 2021)
Visum et Repertum is a statement made by a doctor at the written request of the investigator regarding a medicalexamination of a person whether living, dead or part of the human body made based on oaths for the benefit of the judiciary.To find out the description of the quality level of Visum et Repertum injury at Bhayangkara Hospital Medan. This study uses adescriptive method with a retrospective approach to VeR data on injuries in Bhayangkara Hospital Medan. VeR quality ofinjury at Bhayangkara Hospital in the opening section has a medium quality 75%, the introductory part is 100% good quality,the reporting part is medium quality 56,5%, the conclusion part is 61,5% moderate quality and the closing has good quality100%. The quality of wound injury at Bhayangkara Hospital during January - June 2019 overall have medium quality 60,2%.